2012
DOI: 10.1111/j.1476-5381.2012.02136.x
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of DSS‐induced colitis in mice lacking kinin B1 receptors through compensatory up‐regulation of kinin B2 receptors: the role of tight junctions and intestinal homeostasis

Abstract: BACKGROUND AND PURPOSEKinins are pro-inflammatory peptides that are released during tissue injury, including that caused by inflammatory bowel disease. Herein, we assessed the role and underlying mechanisms through which the absence of kinin B1 receptors exacerbates the development of dextran sulfate sodium (DSS)-induced colitis in mice. EXPERIMENTAL APPROACHB1 and B2 receptor antagonists and B1 receptor knockout mice (B1 -/-) were used to assess the involvement of B1 and B2 receptor signalling in a DSS-coliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 91 publications
(116 reference statements)
0
23
0
3
Order By: Relevance
“…The present study showed that B 2 R was surprisingly overexpressed in the endothelium of thoracic aorta from TGR(Tie 2 B 1 ) rat. This finding was unexpected since a downregulation should occur as a counter regulatory mechanism for overexpression of B 1 R. It has been reported that the lack of one kinin receptor is compensated by the up-regulation of the other subtype, as shown in the case of deletion of B 2 R [10,12,36] and of B 1 R [16,28].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The present study showed that B 2 R was surprisingly overexpressed in the endothelium of thoracic aorta from TGR(Tie 2 B 1 ) rat. This finding was unexpected since a downregulation should occur as a counter regulatory mechanism for overexpression of B 1 R. It has been reported that the lack of one kinin receptor is compensated by the up-regulation of the other subtype, as shown in the case of deletion of B 2 R [10,12,36] and of B 1 R [16,28].…”
Section: Discussionmentioning
confidence: 95%
“…
a b s t r a c tBradykinin (BK) and des-Arg 9 -bradykinin (DBK) of kallikrein-kinin system exert its effects mediated by the B 2 (B 2 R) and B 1 (B 1 R) receptors, respectively. It was already shown that the deletion of kinin B 1 R or of B 2 R induces upregulation of the remaining receptor subtype [10,12,16,28,36]. However studies on overexpression of B 1 R or B 2 R in transgenic animals have supported the importance of the overexpressed receptor but the expression of another receptor subtype has not been determined [17,19,33].
…”
mentioning
confidence: 99%
“…Research has shown B1R itself is able to induce its own expression through the NF-jB pathway, resulting in the elevation of IL-1b and TNFa synthesis (Marcon et al 2013). Another study indicated that B2R expression could be increased in tandem with increased in NF-jB expression (Ricciardolo et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has revealed that B1R and B2R expression is involved in the activation of the NF-jB pathway in osteoblasts, fibroblasts, and colonic epithelial cells (Brechter et al 2008;Marcon et al 2013). There are five NF-jB family members in mammalian hosts, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these authors did not observe changes in the circulating levels of leptin after treatment with kinin B1 receptor antagonist. It has been shown that deletion of one kinin receptor could lead to the modulation of the other kinin receptor expression (Duka et al , 2008 ;Marcon et al , 2013 ). Therefore, the theory could be profered that the kinin B2 receptor could be compensating for the lack of the kinin B1 receptor.…”
Section: Discussionmentioning
confidence: 99%